2003
DOI: 10.1177/039463200301600311
|View full text |Cite
|
Sign up to set email alerts
|

DMSO Modifies Structural and Functional Properties of RPMI-8402 Cells by Promoting Programmed Cell Death

Abstract: Apoptosis in lymphoid cells can be induced in different ways depending on cell type and acquired signal. Biochemical modifications occur at an early phase of cell death while at late times the typical morphological features of apoptosis can be visualized. The aim of this study is to verify by multiparametric analyses the plasma membrane fluidity, the intracellular Ca 2+concentration and the nitric oxide synthase (NOS) activity during cell death progression induced by DMSO treatment. The RPMI·8402 human pre-T I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…It would be interesting to evaluate the possible correlation between response to anti-TNF alpha molecules and molecular or cellular mechanisms of inflammation (apostosis, oxidative stress, lymphocyte and mast cell functions and so on) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to evaluate the possible correlation between response to anti-TNF alpha molecules and molecular or cellular mechanisms of inflammation (apostosis, oxidative stress, lymphocyte and mast cell functions and so on) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that DMSO increases NOS expression and NO probably induces recombinant COX-1 expression by the MT promoter. DMSO also may increase NOS activity in RPMI-8402 cells (Trubiani et al 2003) and astrocytic MT synthesis at the mRNA level (Conklin et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Plasma membrane fluidification is a process that usually accompanies programmed cell death (Ojeda et al, 1995;Trubiani et al, 2003;Christov et al, 2004). Recently, we demonstrated that zinc deficiency promotes cell apoptosis, as evidenced by a higher nuclear fragmentation and poly(ADP-ribose) polymerase (PARP) cleavage .…”
Section: Discussionmentioning
confidence: 99%